Analisis Penerapan Akuntansi Pembiayaan Murabahah Berdasarkan PSAK 102 (Studi Kasus pada KSPPS di Kabupaten Pemalang) - Puspitasari, Saras Meilia; Imron, Ali; Suripto, Suripto (Jurnal Keuangan dan Perbankan, 2023)
This research are purpose as to determine the application and suitability of murabahah financing based on PSAK 102 concerning murabaha accounting for KSPPS BMT Al Fatta, KSPPS Berkah Usaha Syariah, KSPPS Dana Syariah, KSPPS BMT Bina Muamalah Taawun in Pemalang Regency. This study uses a qualitative method with a descriptive approach, namely by describing the implementation of the murabahah financing program, as well as analyzing the suitability of accounting treatment in recognition, measurement, presentation and disclosure murabahah financing through observation, interviews and documentation. The results of this study indicate that the treatment of murabahah financing at KSPPS BMT Al Fatta, KSPPS Berkah Usaha Syariah, KSPPS Dana Syariah, KSPPS BMT Bina Muamalah Taawun located in Pemalang Regency is not fully in accordance with the murabahah accounting treatment in PSAK 102 which includes the recognition and measurement of murabahah. Meanwhile, presentation and disclosure are in accordance with PSAK 102.